2015
DOI: 10.1016/j.indcrop.2015.09.036
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical and biological features of Phyllanthus niruri and Phyllanthus urinaria harvested at different growth stages revealed by 1 H NMR-based metabolomics

Abstract: a b s t r a c tSeveral studies have suggested that plants are potential sources of bioactive compounds. Phyllanthus is a plant genus that has been used in traditional medicine due to its phytomedicinal metabolites content. The variation between two Phyllanthus species (P. niruri and P. urinaria) was studied using proton nuclear magnetic resonance ( 1 H NMR) combined with multivariate data analysis (MVDA). The total phenolic content (TPC), DPPH radical scavenging activity and ␣-glucosidase inhibitory activity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
26
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 33 publications
5
26
0
Order By: Relevance
“…The phenolic compounds and vitamin C exhibits a concentration-dependent manner. The half maximal inhibitory concentration (IC 50 ) of the phenolic compounds is 33.60 μg/mL, which is close to the reported results (28.16 μg/mL) by Mediani (Mediani et al, 2015). IC 50 of vitamin C is 28.43 μg/mL.…”
Section: Antioxidant Activity Analysissupporting
confidence: 87%
“…The phenolic compounds and vitamin C exhibits a concentration-dependent manner. The half maximal inhibitory concentration (IC 50 ) of the phenolic compounds is 33.60 μg/mL, which is close to the reported results (28.16 μg/mL) by Mediani (Mediani et al, 2015). IC 50 of vitamin C is 28.43 μg/mL.…”
Section: Antioxidant Activity Analysissupporting
confidence: 87%
“…Cinnamic acid, gallic acid and quercetin were among the compounds that strongly influenced the discrimination of 1A from 1B ( Figure 4C). The results as shown in Figure 4C,D were consistent with the observations of the loading column plot (Supplementary Materials Figure S3), which suggested that the compounds illustrated in Figure 4C displayed high reliability as chemical markers since their respective standard deviations did not cross the X-axis of the column plot [20]. In contrast, all metabolites in Grade 3 samples (3A and 3U) did not show a strong correlation with their contribution to separation, and this is reflected by the weak separation between clusters in the scores plot ( Figure 4D).…”
Section: Differentiation Of Ajwa Based On Farm Originssupporting
confidence: 85%
“…(26) Mediani, et al, reported that P. niruri contained a high amount of rutin, followed by gallic acid, quercetin. (27) The phenolic compound gallic acid and ellagic acid found in P. niruri have been demonstrated to possess antioxidant activity and cancer chemopreventive abilities. (28) Rutin can reduce the risk of arteriosclerosis, anti-inflammatory and vasoactive properties, reduce coronary heart disease, and anticancer properties.…”
Section: Frap Activitymentioning
confidence: 99%